Models and interventions to promote and support engagement of first nations women with maternal and child health services : an integrative literature review - Austin, Catherine; Hills, Danny; Cruickshank, Mary (Children, 2022)
Background: Studies show that participation in maternal and child health (MCH) services improves health outcomes for First Nations families. However, accessing MCH services can be associated with fear, anxiety, and low attendance at subsequent appointments. Objective: To identify the existing knowledge of models/interventions that support engagement of First Nations women with MCH services in the child’s first five years. Methods: An integrative review was undertaken of full-text, peer-reviewed journal articles and grey literature, which were analysed to identify barriers and enabling factors that influenced the engagement of First Nations families with MCH services. Results: Enabling factors that influenced the engagement with MCH services included service models/interventions that are timely and appropriate, and effective integrated community-based services that are flexible, holistic, culturally strong, and encourage earlier identification of risk and further assessment, intervention, referral, and support from the antenatal period to the child’s fifth birthday. Barriers to engagement included inefficient communication, lack of understanding, cultural differences between the client and the provider, poor continuity of care, limited flexibility of service delivery to meet individual needs, and a health care model that does not recognise the importance of the social determinants of health and wellbeing. Discussion: Timely, effective, holistic engagement with First Nations women during their child’s first 2000 days, which respects their culture and facilitates genuine partnerships built on co-design and shared decision making with the indigenous community, needs to be an essential part of the MCH service model if health care providers seek to practise within First Nations communities. Conclusion: Improving engagement with MCH services is important for First Nations families, the nursing practice, and public health. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.